Respostas
respondido por:
1
Olá!!!!
Resolução!!
3 (1/3 - x) - (- 2x + 5) = -3
3/3 - 3x + 2x - 5 = - 3
1 - 3x + 2x - 5 = - 3
- 3x + 2x = - 3 - 1 + 5
- x = - 4 + 5
- x = 1 ( - 1 )
x = - 1
S = { - 1 }
Espero ter ajudado...
Resolução!!
3 (1/3 - x) - (- 2x + 5) = -3
3/3 - 3x + 2x - 5 = - 3
1 - 3x + 2x - 5 = - 3
- 3x + 2x = - 3 - 1 + 5
- x = - 4 + 5
- x = 1 ( - 1 )
x = - 1
S = { - 1 }
Espero ter ajudado...
respondido por:
1
Olá, boa noite ☺
Resolução:
3(1/3 - x) - (-2x + 5) = -3
3/3 - 3x + 2x - 5 = -3
1 - 3X + 2X - 5 = -3
-3X + 2X = -3 - 1 + 5
-x = 1 .(-1)
x= -1
Bons estudos ✨
Resolução:
3(1/3 - x) - (-2x + 5) = -3
3/3 - 3x + 2x - 5 = -3
1 - 3X + 2X - 5 = -3
-3X + 2X = -3 - 1 + 5
-x = 1 .(-1)
x= -1
Bons estudos ✨
Perguntas similares
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás